2021
DOI: 10.21037/aes-20-114
|View full text |Cite
|
Sign up to set email alerts
|

Combined automated screening for age-related macular degeneration and diabetic retinopathy in primary care settings

Abstract: Background: Age-related macular degeneration (AMD) and diabetic retinopathy (DR) are among the leading causes of blindness in the United States and other developed countries. Early detection is the key to prevention and effective treatment. We have built an artificial intelligence-based screening system which utilizes a cloud-based platform for combined large scale screening through primary care settings for early diagnosis of these diseases. Methods: iHealthScreen Inc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…It is well established that deep learning approaches perform well on pattern recognition tasks in imaging data (Ting et al 2019). Numerous approaches have been explored including classification of disease activity in AMD on optical coherence tomography (OCT) scans (Lee, Baughman & Lee 2017, Hwang et al 2019, Motozawa et al 2019, detection of referrable disease on fundus images (Burlina et al 2018, Bhuiyan et al 2021) and quantifying pathological fluid by segmentation of OCT images (De Fauw et al 2018, Schlegl et al 2018, Gao et al 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that deep learning approaches perform well on pattern recognition tasks in imaging data (Ting et al 2019). Numerous approaches have been explored including classification of disease activity in AMD on optical coherence tomography (OCT) scans (Lee, Baughman & Lee 2017, Hwang et al 2019, Motozawa et al 2019, detection of referrable disease on fundus images (Burlina et al 2018, Bhuiyan et al 2021) and quantifying pathological fluid by segmentation of OCT images (De Fauw et al 2018, Schlegl et al 2018, Gao et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“… 2018 , Bhuiyan et al . 2021 ) and quantifying pathological fluid by segmentation of OCT images (De Fauw et al . 2018 , Schlegl et al .…”
Section: Introductionmentioning
confidence: 99%
“… 40 This study reported 23 of 36 of the transparency parameters we outlined. 40 Two studies used the STARD reporting checklist, and they reported 14 of 36 46 and 19 of 21 56 of the transparency parameters we assessed. These relatively low numbers are in part because many of the factors we reviewed were at the level of model development, not only clinical trialing.…”
Section: Discussionmentioning
confidence: 99%
“…The iPredict AI Eye Screening System offers fully automated diagnosis of referable DR (sensitivity of 97.0% and specificity of 96.3%) and AMD (sensitivity of 86.6% and specificity of 92.1%) by analyzing CFPs [89] The Vision Academy recognizes the advantages of AI technology and recommends the use of them to be of additive and synergistic value to current standards of care. In terms of applying such technologies in diagnosing and screening retinal diseases, we summarize the following directions and emphasize several viewpoints important for the future.…”
Section: Current Developments Future Directions and Vision Academy Re...mentioning
confidence: 99%